Modern technologies for radiofrequency pulmonary vein isolation. Comparison of radiofrequency balloon catheter with high power-short duration ablation in patients with paroxysmal atrial fibrillation. (19th May 2022) - Van Den Bruck, J-H; Sultan, A; Woermann, J; Filipovic, K; Erlhoefer, S; Arica, Z; Scheurlen, C; Dittrich, S; Schipper, J-H; Lueker, J; Steven, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Pulmonary vein isolation (PVI) is an established therapy for symptomatic atrial fibrillation (AF). Traditional point by point ablation can be time consuming requiring advanced training. Novel radiofrequency (RF) ablation techniques sought to facilitate PVI. Point by point ablation using high power short duration (HPSD) settings has already shown to be safe and effective whereas there is paucity of data using a novel multi-electrode balloon catheter (Heliostar™, Biosense Webster, CA, USA). Purpose: We aimed to assess procedure characteristics, efficacy, and safety of the Heliostar™ RF-balloon catheter in direct comparison with the latest RF ablation technique. Methods: All patients undergoing PVI using the Heliostar™ between September and November 2021 were included in this ongoing single center registry. Procedural data and outcome were assessed and compared with data from patients undergoing initial PVI for paroxysmal AF with the HPSD approach from our specifically designed database. A power setting of 70W/7s (70W/5s at posterior wall) was considered as HPSD. Results: A total of 51 consecutive patients (61±16 years, 49% male) were included. Of those 13 patients undergoing RF-balloon and 38 patients HPSD ablation. Baseline parameters did not differ between groups. Acute PVI was achieved in all patients. For every RF-application with the RF-balloon all necessary criteria were met: Inflation index was between 0.9 and 1.0 and a minimum of 9/10 electrodes were within impedance range. A mean of 2.8±1.4 applications per vein (LSPV 3.2±2.9, LIPV 2.6±2.5, RSPV 2.8±2.0 and RIPV 1.8±0.8) were necessary to achieve durable isolation. The mean maximum esophageal temperature was 40.2±0.8°C. When comparing procedural parameters with HPSD no statistically significant difference was seen regarding procedure duration (Heliostar™ 111±28min and HPSD 100±25min; p=0.3) and left atrial dwell time (Heliostar™ 90±23min and HPSD 80±26min; p=0.08). Fluoroscopy time (Heliostar™ 17±4min and HPSD 13±5min; p=0.005) and dose (Heliostar™ 3961±1325mGy*cm2 vs. HPSD 3153±1833mGy*cm2; p=0.04) were higher in the Heliostar™ group. No major complication occurred in both groups. A three month follow up was available for 10 patients in the Heliostar™ and for 38 patients in the HPSD group. All 10 Heliostar™ patients and 79% of the HPSD patients were free from atrial arrhythmias at follow up. Conclusion: The novel multi-electrode RF-balloon has shown to be safe and effective in the first clinical routine AF ablation procedures. The tendency towards longer LA dwell times, procedure durations and the significantly higher fluoroscopy exposition in comparison with the HPSD PVI can be attributed to the learning curve applying a new ablation system. More experience is needed in the future to determine the benefits of the novel RF-balloon.